“They are just five-year-old boys”: Examining the role of childhood innocence in the early normalization of sexual violence - Prioletta, Jessica (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2023)
The purpose of this article is to examine how the discourse of childhood innocence masks the ways in which sexual violence by boys against girls is perpetrated in kindergarten. Findings from a year-long ethnographic study conducted in two Canadian kindergarten classrooms show that narrow understandings of gender and sexuality in childhood obscure schools’ responses to problematic gendered behaviors enacted by certain boys. The author contends that in failing to attend to gender and sexuality with young children, kindergarten education may contribute profoundly to the early normalization of sexual violence. The article concludes with a discussion on the role that kindergarten education can play in countering sexual violence inside and outside of schools.